The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ente.202100546
|View full text |Cite
|
Sign up to set email alerts
|

Silver Oxygen Reduction Electrocatalyst in Alkaline Medium: Aging and Protective Coating

Abstract: The oxygen reduction reaction (ORR) is a key process in anion exchange membrane fuel cells. The alkaline conditions should allow silver‐based cost‐efficient catalysts to replace platinum group metal materials. However, Ag electrochemical stability or lack of stability in alkaline medium is still to be demonstrated. Herein, Ag catalyst nanoparticles (NPs) are characterized by identical location transmission electron microscopy and X‐ray photoelectron spectroscopy after electrochemical cycling, revealing the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…45−47 The PDA coating can prevent leaching in the aqueous environment. 44 In addition, a thin layer of PDA on Ag NCs improves the sensing of biological molecules through π−π interactions and hydrogen bonds. 14 In our r e s e a r c h , t h e P D A c o a t i n g w a s d o p e d w i t h hexachloroplatinate(IV) complexes at varying concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…45−47 The PDA coating can prevent leaching in the aqueous environment. 44 In addition, a thin layer of PDA on Ag NCs improves the sensing of biological molecules through π−π interactions and hydrogen bonds. 14 In our r e s e a r c h , t h e P D A c o a t i n g w a s d o p e d w i t h hexachloroplatinate(IV) complexes at varying concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…For this, plasmonic metal core dielectric shells were synthesized. Silver NC (and NW) cores were coated with the polydopamine (PDA) nanometric shell using a technique developed in our laboratory, and we adapted it to differently sized silver NCs with different thickness coatings. PDA is a final oxidation product of dopamine-HCl or other catecholamines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver is a potential alternative electrocatalyst for hydrogen fuel cells. This is because Ag has similar properties to Pt [13][14][15]. In addition, Ag-based catalysts are 50 times cheaper than the industrial Pt/C standard [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is because Ag has similar properties to Pt [13][14][15]. In addition, Ag-based catalysts are 50 times cheaper than the industrial Pt/C standard [14]. Previous studies have revealed that Ag nanowires, nanocubes, and nanoparticles have high catalytic performance due to their unique surface morphology [16].…”
Section: Introductionmentioning
confidence: 99%